Conflicts Associated with Dam Removal in Sweden - Anna G. C. Lejon (Ecology and Society, 2009)
The increasing number of deteriorating old dams that need renovation or have lost their function make dam removal a viable management option. There are at least four major reasons for dam removal: safety, law and policy, economy, and ecology. Here we discuss 17 Swedish dams that were recently considered for removal. Because dam removal usually causes controversy, dam removal initiatives may succeed, fail, or result in a compromise such as a bypass channel for migrating fish. We identify and discuss three major obstructions to dam removal: funding, cultural-historical values, and threatened species. To facilitate dam removal, the reasons for, and the effects of, dam removal must be carefully explained, and the public and stakeholders must be kept informed. In complicated cases in which compromise solutions may be the most feasible outcome, the integration of the knowledge of different stakeholders is crucial. The involvement of diverse stakeholders increases their willingness to find compromises, thus avoiding conflicts and failures.